2022
DOI: 10.1101/2022.06.30.498318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arabidopsis FIBRILLIN6 regulates carotenoid biosynthesis by directly promoting phytoene synthase activity

Abstract: Carotenoids are health-promoting plastidial isoprenoids with essential functions in plants as photoprotectants and photosynthetic pigments in chloroplasts. They also accumulate in specialized plastids named chromoplasts, providing color to non-photosynthetic tissues such as flower petals and ripe fruit. Carotenoid accumulation in chromoplast requires specialized structures and proteins such as fibrillins. Although fibrillins were first reported as structural components of carotenoid sequestering structures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…119 Arabidopsis FBN6 could interact with PSY to promote its enzymatic activity, hence impacting the metabolic flux of the carotenoid pathway. 120 In melon, CmOR physically interacted with CmFBN1 and greatly stabilized CmFBN1, which stimulated plastoglobules proliferation and subsequently carotenoid accumulation in chromoplasts. 106 For algae, Dunaliella accumulates β-carotene in plastoglobules within the chloroplast, whereas H. pluvialis deposits astaxanthin in cytoplasmic lipid droplets 121 (Figure 1).…”
Section: Carotenoid-sequestering Structuralmentioning
confidence: 99%
See 1 more Smart Citation
“…119 Arabidopsis FBN6 could interact with PSY to promote its enzymatic activity, hence impacting the metabolic flux of the carotenoid pathway. 120 In melon, CmOR physically interacted with CmFBN1 and greatly stabilized CmFBN1, which stimulated plastoglobules proliferation and subsequently carotenoid accumulation in chromoplasts. 106 For algae, Dunaliella accumulates β-carotene in plastoglobules within the chloroplast, whereas H. pluvialis deposits astaxanthin in cytoplasmic lipid droplets 121 (Figure 1).…”
Section: Carotenoid-sequestering Structuralmentioning
confidence: 99%
“…Recently, it was found that Arabidopsis FBN2 could interact with other proteins involved in various metabolic processes, including CCD4, a plastoglobules-associated enzyme involved in carotenoid degradation, but the functional relevance of the interaction with CCD4 was not explored Arabidopsis FBN6 could interact with PSY to promote its enzymatic activity, hence impacting the metabolic flux of the carotenoid pathway . In melon, CmOR physically interacted with CmFBN1 and greatly stabilized CmFBN1, which stimulated plastoglobules proliferation and subsequently carotenoid accumulation in chromoplasts .…”
Section: Regulation Of Carotenoid Biosynthesis By Regulators In Plant...mentioning
confidence: 99%
“…The same authors have shown that homozygous Arabidopsis mutants with the FBN5 encoding gene knocked out were seedling-lethal, and the growth rate of transgenic plants with low FBN5-B levels was slower than that of wild-type plants. FBN6 was shown to interact with PSY and increase its enzymatic activity [72].…”
Section: Carotenoid Synthesismentioning
confidence: 99%